Adolescents With Cancer Need Trustworthy Information and Prefer to Receive It From a Human Source Rather Than From the Internet: A Qualitative Study - Schwartz-Attias, Irit; Raz, Haya; Natanzon-Bracha, Tamar; Finkelstein, Adi; Kreitler, Shulamith (Frontiers in Psychology, 2021)
Background: In pediatric cancer, the legal obligation to provide information is usually toward the parents who are the authorized signatories of the informed consent form. It is now known that aside from providing information to the parents, it is also very important to provide information to the children and adolescents themselves. The question is how the adolescents relate to this. What information do they already possess and what would they like to know? Would they wish to hear the truth in all situations and at what stage? What are their preferred sources of information? Method: A qualitative study that included in-depth interviews with 19 adolescents with cancer, aged 8.5–18, who were receiving active treatments and had been diagnosed at least 1 month previously. The interviews were guided by 15 open-ended questions. Findings: The analysis of the interviews indicated that adolescents know quite a lot about the course of their disease and the information they lack is mainly etiological. The participants reported a lack of knowledge concerning sexuality and a sense of discomfort talking about it, leaving them with open questions. They all claimed that it is important to tell the truth: “Even if the truth is difficult, it is important to tell it.” The participants reported that information can be scary, so it must be structured and adapted to the age and emotional readiness of the individual. Most of the participants prefer not to use the internet as an information resource due to the profusion of stressful and non-adapted information. Conclusion: Adolescents with cancer need trustworthy information and prefer to receive it from a human source rather than from the internet. Not telling the truth can lead them to feel fear and loneliness. The medical staff must operate in sensitive and creative ways to provide adolescents with access to information on various subjects, including sexuality, which they are ashamed to talk about, leaving them with a sense of shame and a lack of knowledge in this area.